2016
DOI: 10.1002/2016jc011906
|View full text |Cite
|
Sign up to set email alerts
|

Chromophoric and fluorescent dissolved organic matter in and above the oxygen minimum zone off Peru

Abstract: As a result of nutrient upwelling, the Peruvian coastal system is one of the most productive regions in the ocean. Sluggish ventilation of intermediate waters, characteristic for the Eastern Tropical South Pacific (ETSP) and microbial degradation of a high organic matter load promotes deoxygenation at depth. Dissolved organic matter (DOM) plays a key role in microbial respiration and carbon cycling, but little is known on DOM distribution and cycling in the ETSP. DOM optical properties give important insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 116 publications
(244 reference statements)
1
64
0
Order By: Relevance
“…In situ fluorometry provided an opportunity to study FDOM distribution in greater detail and commercially available FDOM fluorometers are usually built to detect humic substances Belzile et al, 2006;Kowalczuk et al, 2010;Aiken et al, 2011;Loginova et al, 2016). In this study we simultaneously measured three different FDOM components, and the most interesting feature observed with the use of this new instrument was very significant spatial coupling between I CH3 and I FChla .…”
Section: Distribution Of Fdom Components In the Ocean And Their Depenmentioning
confidence: 77%
“…In situ fluorometry provided an opportunity to study FDOM distribution in greater detail and commercially available FDOM fluorometers are usually built to detect humic substances Belzile et al, 2006;Kowalczuk et al, 2010;Aiken et al, 2011;Loginova et al, 2016). In this study we simultaneously measured three different FDOM components, and the most interesting feature observed with the use of this new instrument was very significant spatial coupling between I CH3 and I FChla .…”
Section: Distribution Of Fdom Components In the Ocean And Their Depenmentioning
confidence: 77%
“…C1 displayed two excitation maxima at 250 and 365 nm and one emission maxima at 456 nm. Similar fluorescence signatures are initially categorized as representing a mixture of terrestrial humic‐like fluorescence peaks A and C (Coble, ) but have also been widely observed in oceanic waters (Catalá et al, ; Guéguen et al, ; Jørgensen et al, ; Kowalczuk et al, ; Loginova, Thomsen, & Engel, ; Yamashita et al, ). C2 had excitation/emission maxima at 250, 330/388 nm, consistent with marine humic‐like fluorescence (peak M; Coble, ), which has been characterized as representing microbially altered DOM (Stedmon & Markager, ; Yamashita et al, ).…”
Section: Resultsmentioning
confidence: 95%
“…Genes encoding peptidases are also highly represented in both PN262000N21 and ARCTIC96B-7 (51 and 37 in each respectively), presumably for use in hydrolysing primary or secondary production available as dissolved or particulate organic matter. The organic matter pool in OMZ environments has not been extensively characterized (Loginova et al, 2016). However, subeuphotic marine areas are often enriched in semi-labile dissolved organic matter (Moran et al, 2016).…”
Section: A Pn26000n21 Protein Coding Genes Involved In Inorganic Biomentioning
confidence: 99%